PENGARUH MARKETPLACE DALAM MENINGKATKAN DAYA SAING EKONOMI KREATIF PADA UMKM D’ELIXIR - Ivtachul Ma’rifah; Bella Rizka Indah W; Erren Imaniar Rizqi; Nanik Kustiningsih (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
Through the marketplace platform Shopee, and Tokopedia, this research was conducted to see how much influence it has in increasing the competitiveness of D'Elixir MSME products. The research method used is a quntitative method through the process of observation, interviews, and document studies. This study obtained respondents as many as 25 shopee and tokopedia users as well as three D'Elixir MSME owners. The results of this study indicate that the marketplace has a major influence in increasing the competitiveness of D'Elixir's MSME gift products with other similar products as evidenced by a significant increase in profit. With the use of the marketplace, goods can be easily searched by customers and marketed widely. By using a marketplace, sellers can save on production costs and increase the ease of transacting online. This can have an impact on increasing competitiveness for D'Elixir MSMEs